The Impact of Tax Changes on the Short-run Investment Behaviour of New Zealand Firms - Richard Fabling; Richard Kneller; Lynda Sanderson (New Zealand Government, The Treasury, 2015)
This paper examines firm-level investment responses to exogenous changes in the forward looking user cost of capital associated with reforms to the corporate and personal tax system over the last decade. Adjustments to personal tax rates and fiscal depreciation allowances provide a direct lever through which government policy can affect the cost of capital faced by firms. The effect of these tax adjustments differs across firms according to their asset structure, providing both inter-temporal and inter-firm variation in UCCs and enabling an assessment of the short-run impact of UCC changes on investment behaviour. This analysis shows that while tax-induced changes in the UCC have significantly affected investment behaviour among some firms, the aggregate impacts are likely to have been negligible as the industries in which investment impacts are observed make a very small contribution to aggregate investment.
Keywords: D22; H20; 330; Unternehmensbesteuerung; Einkommensteuer; Investition; Kapitalkosten; Neuseeland